Design and implementation of society and club management system in UiTM / Noraini Johari - Johari, Noraini (2006)
Design and Implementation of Society and Club Management in UiTM is the name of the system. This system is basically develops for student in UiTM.The system is developed due to the problem that arise using manual information and difficult to know what activity that society and club to do. As for the solving this problem, design and implementation of society and club management system need to build as the objective is to give more benefit to the students and helping them in getting information faster and efficient. The users of this web site are student, HEP staffs and system admin that have different level of user. The components of this system include forum, sms, and messages board. The system enable and easy of management of student activity. Data and information have been collected by doing research, interview, and study fi-om book and internet. This web site used a methodology called System Development Life Cycle (SDLC) was applied in this system. This system also integrates several software packages and programming languages suitable for the development process. Finally, it is hope this web site would greatly benefit to all people who involve with it.